Hierarchical modelling of volatility spillovers in ship demolition markets - Abdullah Açik (Scientific Journal of Gdynia Maritime University, 2021)
he offered demolition prices are as important as the freight rates in the market in shipowners' decisions to send their ships for demolition. This study aims to determine the most affected and the most affecting countries in the ship demolition market by examining the hierarchical price movements among the prices offered for demolition in major centres around the world. In this direction, integrated causality in variance, Interpretative Structural Modeling (ISM) and MICMAC (Matrices d’Impacts cross-multiplication appliqúe a classmate) analysis are used. According to the obtained results, the price dependence on Turkey is the lowest, while the price dependence in Bangladesh is the highest. Volatility in the market is spreading to other markets from Turkey. These results are thought to be useful in understanding price behaviour in the ship demolition industry, which is a relatively small market.